Weathered Mississippi Canyon 252 crude oil ingestion alters cytokine signaling, lowers heterophil:lymphocyte ratio, and induces sickness behavior in zebra finches (Taeniopygia guttata). (December 2020) - Goodchild, Christopher G.; Love, Ashley C.; Krall, Jeffrey B.; DuRant, Sarah E.
Abstract: The Deepwater Horizon (DWH) oil spill caused an estimated 100, 000 bird mortalities. However, mortality estimates are often based on the number of visibly oiled birds and likely underestimate the true damage to avian populations as they do not include toxic effects from crude oil ingestion. Elevated susceptibility to disease has been postulated to be a significant barrier to recovery for birds that have ingested crude oil. Effective defense against pathogens involves integration of physiological and behavioral traits, which are regulated in-part by cytokine signaling pathways. In this study, we tested whether crude oil ingestion altered behavioral and physiological aspects of disease defense in birds. To do so, we used artificially weathered Mississippi Canyon 242 crude oil to orally dose zebra finches ( Taeniopygia guttata ) with 3.3 mL/kg or 10 mL/kg of crude oil or a control (peanut oil) for 14 days. We measured expression of cytokines (interleukin [IL]-1β, IL-6, IL-10) and proinflammatory pathways (NF-κB, COX-2) in the intestine, liver, and spleen (tissues that exhibit pathology in oil-exposed birds). We also measured heterophil:lymphocyte (H:L) ratio and complement system activity, and video-recorded birds to analyze sickness behavior. Finches that ingested crude oil exhibited tissue-specific changes in cytokine mRNA expression. Proinflammatory cytokine expression decreased in the intestine but increased in the liver and spleen. Birds exposed to crude oil had lower H:L ratios compared to the control on day 14, but there were no differences in complement activity among treatments. Additionally, birds exposed to 10 mL/kg crude oil had reduced activity, indicative of sickness behavior. Our results suggest cytokines play a role in mediating physiological and behavioral responses to crude oil ingestion. Although most avian population damage assessments focus on mortality caused by external oiling, crude oil ingestion may also indirectly affect survival by altering physiological and behavioral traits important for disease defense. Graphical abstract: Image 1 Highlights: Crude oil ingestion alters cytokine mRNA expression in tissues. Oil-exposed birds had a lower heterophil:lymphocyte ratio. Oil-exposed birds induced sickness behaviors. Altered cytokine expression may contribute to immunotoxicity. Abstract : Crude oil ingestion impaired physiological and behavioral components of disease defense, which may be partially attributable to shifts in cytokine mRNA expression.